Comprehensive Facts of Working Stress Environment among BPO Workers: Special Reference to Drug Abuse and Family Fighting: Exploring the Impact of Work Stress on BPO Workers and Strategies for Stress Management (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Work stress is characterized as the hurtful physical and emotional responses that happen when work necessities don't coordinate the worker's capacities, resources, and requirements .Especially more consideration given to the Business Process Outsourcing (BPO). In present world, BPO undertaking is expanding in Business dependent on their customer. In this circumstance employee must lift up their vitality and job in this association, and they befuddled to do in their job. It prompts stress, strain, and anxiety to the employee. So this paper reveals the reason which give a mentally as well as physical problems as an effect of occupational stress among BPO Workers. This paper also deals with the management criteria and techniques to control stress among the workers of BPO.